Ukuran Perusahaan Dan Tata Kelola Dalam Mengungkapkan Modal Intelektual - Liana Susanto, Viriany, Henny Wirianata, Amin Wijoyo, (Jurnal Ekonomi, 2021)
The research data processed is from the 2016 – 2018 financial report for the manufacturing industry registered in IDX. Sample data were taken purposive random sampling. Data processing and analysis with data panel regression using the Eviews 10 program. From the results of the data found that significantly the size of the company and GCG has an influence over the disclosure of intellectual capital. The company's size variable indicates it has a positively significant influence. Meanwhile, of the five components of GCG tested, only the size of the board of directors partially positively influenced the level of disclosure about intellectual capital. Other GCG variables, namely independent commissioners, audit committees, and institutional ownership, have no significant influence.